The Effect Of Ecoenzyme Spraying On The Number Of Leaves Of Spinach (Amaranthus hybridus L.) Cultivated Hydroponically. - Sabrina Aprilia, Dhea; Fevria, Resti; Vauzia; Advinda, Linda (Jurnal Serambi Biologi, 2022)
Spinach is one of the vegetables favored by the people of Indonesia and also has high nutritional value. Spinach can be cultivated conventionally or hydroponically. Hydroponics is one solution to the problem of limited land in farming that uses water as a nutrient medium that will be directly absorbed by plants to support plant growth. Hydroponics uses Ab-Mix nutrients. To get better results, ecoenzyme can be used as a support for plant fertilizers. This study aims to see the effect of spraying ecoenzyme on the number of spinach leaves. This study is an experimental study consisting of 5 treatments and 5 replications with a dilution of ecoenzyme solution, P1 (control), P2 (2mL ecoenzyme + 1L water), P3 (3mL ecoenzyme + 1L water), P4 (4mL ecoenzyme + 1L water), and P5 (5mL ecoenzyme + 1L water). The data obtained were analyzed by means of variance (ANOVA) with Duncan's New Multiple Range Test (DNMRT) further test. The results showed that spraying ecoenzyme on spinach plants had no effect on the number of plant leaves.